The change from a pastoral of “maintenance” to one of the integral development of the person - Jerí Tafúr, Alfredo (2020)
This paper is an academic reflection within the pastoral area, which involves a theological reflection inasmuch as it has to do with Christian practices and the way to announce the Good Word. Pandemic times provide a good opportunity to reinvent new strategies for pastoral work: ones that are nearer, more engaged in history, open to dialogue and with a better understanding of the person and its integrity. It is important to understand that times have changed and thus the way to announce the faith in Jesus Christ needs to change as well. We need to move from a pastoral focused on morality and the obedience of precepts and external norms, to one that truly fill the person with a deep experience of God. This lively encounter with him will determine the way to understand religion as a relation with God, oneself, and others.